How to Obtain High‐Quality Metaphase Spreads for Molecular Cytogenetics. Issue 2 (25th February 2022) - Liehr, Thomas; Weise, Anja; Person, Luisa; Padutsch, Niklas; Kankel, Stefanie
Abstract: Interphase or metaphase nuclei can be accessed in molecular cytogenetic analyses. Metaphase spreads are routinely studied by fluorescence in situ hybridization (FISH) to answer clinical genetic questions. Even though metaphase quality is essential for FISH studies, there is limited ability in clinical cases to improve the quality of cytogenetic preparations. However, the quality of preps is important for the exact localization of FISH signals, which is necessary to identify individual chromosomes and chromosomal sub‐regions using inverted DAPI banding. Here we present an efficient and easy‐to‐perform variant of standard slide pretreatment before a normal FISH procedure. This method reproducibly leads to solid, "steel, " nonfuzzy, and well‐DAPI‐banded metaphases. This protocol works in blood lymphocyte and amniotic fluid‐derived fibroblasts. © 2022 The Authors. Current Protocols published by Wiley Periodicals LLC. Basic Protocol : Slide pretreatment for high‐quality metaphases for molecular cytogenetics.